2019
DOI: 10.3389/fchem.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Toward Highly Dispersed Mesoporous Bioactive Glass Nanoparticles With High Cu Concentration Using Cu/Ascorbic Acid Complex as Precursor

Abstract: Copper (Cu) ions have a variety of advantageous biological functionalities, such as proangiogenic and bactericidal activities. Given the intrinsic biodegradability and biocompatibility, silicate-based mesoporous bioactive glass nanoparticles (MBGNs) are considered as promising platforms for the delivery of Cu ions. However, effective incorporation of Cu into MBGNs still faces challenges, e.g., particle aggregation, the formation of insoluble crystalline Cu-based nanoparticles, and a low loading amount of Cu. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 63 publications
12
67
0
2
Order By: Relevance
“…As shown in Figure 5B, zeta potential of the MBGs changes from 5 mV for Ca-MBG group (parent glass) to −16, −6, −12 mV for Sr-, Co-, and Sr-Co-MBG groups, respectively. A similar phenomenon was reported elsewhere for Cu-doped MBGs [42]: the increased zeta potential values may be related to the elevated amounts of positively charged ions in MBGs structure as well as the quick release of the dopants used. It has been previously reported that the surface charge of MBGs have significant effects from a biological viewpoint [43][44][45].…”
Section: Discussionsupporting
confidence: 83%
“…As shown in Figure 5B, zeta potential of the MBGs changes from 5 mV for Ca-MBG group (parent glass) to −16, −6, −12 mV for Sr-, Co-, and Sr-Co-MBG groups, respectively. A similar phenomenon was reported elsewhere for Cu-doped MBGs [42]: the increased zeta potential values may be related to the elevated amounts of positively charged ions in MBGs structure as well as the quick release of the dopants used. It has been previously reported that the surface charge of MBGs have significant effects from a biological viewpoint [43][44][45].…”
Section: Discussionsupporting
confidence: 83%
“…S2a ) shows the sphere-like shape of the particles with a particle size of ~100 nm. The morphology of MBGNs was in good agreement with that of mesoporous silicate nanoparticles synthesized using similar methods [ 20 , 23 ]. The mesoporous structure, large specific surface area and pore volume of MBGNs have been confirmed in our previous study [ 20 ].…”
Section: Resultssupporting
confidence: 66%
“…The morphology of MBGNs was in good agreement with that of mesoporous silicate nanoparticles synthesized using similar methods [ 20 , 23 ]. The mesoporous structure, large specific surface area and pore volume of MBGNs have been confirmed in our previous study [ 20 ]. The morphological characteristics of MBGNs were expected to enhance the dispersion in polymeric matrices and interactions with polymeric molecules towards a more integrated structure [ 13 , 24 ].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Adding to this, the mesoporous nanoparticle form of bioactive glass has the capacity to intracellular deliver therapeutic molecules (drugs, growth factors, or genes) [ 16 ]. Some of the recent studies have reported that mesoporous bioactive glass nanomaterials and their composites/hybrids could demonstrate the capacity for delivering drugs and genes, as well as releasing bioactive ions [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%